Studying the Role of Vegetarianism as a Potential Strategy for Cancer Prevention and Treatment, a Bibliometric Analysis - Maria Chrysafi; Maria Gialeli; Constantinos Giaginis; Andreas Y. Troumbis; Georgios K. Vasios (Epidemiologia)
Vegetarianism, as a dietary pattern, is characterized by animal product avoidance and increased consumption of fruits, vegetables, whole grains, and legumes. It has been associated with health benefits, both physical and psychological, and has raised interest as a potential strategy for cancer prevention and treatment, which remains one of the leading causes of morbidity and mortality worldwide, demanding continual exploration of novel approaches. Background/Objectives: This study aims to describe trends in scientific publications about the relationship between vegetarianism and cancer and to highlight research gaps using bibliometric analysis. Methods: The methodology includes comprehensive research of three literature databases. After combining and cleaning these data, a final sample of 3427 studies was obtained that was analyzed using the Bibliometrix-R package. Results: The results indicate a continuously growing production of scientific publications. The most impactful sources, authors and their collaborations were identified. Author keywords, their co-occurrence network, and thematic trends were studied. Conclusions: Through synthesizing and critically evaluating insights from the scientific literature, we aim to contribute to the understanding of the potential benefits of vegetarianism in cancer prevention and management. However, due to the complexity of the topic, the results are often contradictory and could be used as a starting point for further research.